2006
DOI: 10.1002/adfm.200600760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanotube Functionalization on the Coefficient of Thermal Expansion of Nanocomposites

Abstract: Single‐walled carbon nanotubes (SWNTs) are functionalized through both covalent and noncovalent bonding approaches to enhance dispersion and interfacial bonding. The coefficient of thermal expansion (CTE) of the functionalized‐SWNT‐reinforced epoxy composites are measured with a thermal mechanical analyzer (TMA). Experimental results indicate that changes of the glass‐transition temperature (Tg) in functionalized SWNT–polymer composites are dependent upon the functionalization methods. The CTE below the glass‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
98
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 24 publications
(23 reference statements)
8
98
2
Order By: Relevance
“…Wang et al 23 also observed a thermal expansion coefficient close to 6.5 3 10 25 8C 21 before T g for an epoxy system and values in the range of 6 to 3 3 10 25 8C 21 for nanocomposites based on pristine and modified SWNTs.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Wang et al 23 also observed a thermal expansion coefficient close to 6.5 3 10 25 8C 21 before T g for an epoxy system and values in the range of 6 to 3 3 10 25 8C 21 for nanocomposites based on pristine and modified SWNTs.…”
mentioning
confidence: 83%
“…However, the processing variables are as important as the formulation, and the use of a surfactant and a solvent in a dispersion stage led to a decrease in T g in SWNT/epoxy materials in the work of Liao et al, 9 for instance. Moreover, the 23 also shows a decrease in the epoxy/SWNT glass transition for both pristine and functionalized CNTs. In this work, the differences related to the main transition are in the range of T g accuracy both for series 1 and 2.…”
Section: Thermal Analysismentioning
confidence: 94%
“…We thus compiled and analyzed data values of glass transition temperature of CNT/epoxy composites from different articles. The CNT used in these works were unmodified MWNT [8][9][10][11][12][13][14][15][16] or unmodified SWNT [5,[17][18][19][20][21][22]. The data relative to preparation method of the composites, glass transition temperature and its measurement method are summarized in Table 1.…”
mentioning
confidence: 99%
“…The number of publications specifically investigating the thermal expansion of nanocomposites, rather than bulk materials, is relatively limited. [8][9][10][11][12] Through the use of molecular dynamics (MD) simulations, Wei et al observed a signifi cant increase of the α for SWNT-polyethylene composites above T g and attributed this to an equivalent increase in the excluded volume of the embedded CNTs as a function of temperature. [ 9 , 10 ] Other studies have shown that the α of the composite above its T g can be tuned by nanotube functionalization.…”
Section: Doi: 101002/adma201003145mentioning
confidence: 99%